Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena CEO Faculty Programme “Driving Six Sigma Quality In Industry 2016" - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
We must acknowledge the fact that dynamism in the way we think, the way we act and the way teaching and learning process is carried out is the way forward for our higher education system. The approach in teaching and learning for example, must not be confined within the traditional setting, thus the introduction of the CEO Faculty Programme is an innovative attempt to enhance knowledge and information gathering by our students through their interaction with the leading figures of the industry.